2008
DOI: 10.1007/s10694-007-0036-2
|View full text |Cite
|
Sign up to set email alerts
|

Study of Water Droplet Behavior in Hot Air Layer in Fire Extinguishment

Abstract: Evaporation of water droplets while traveling in hot air layer will be studied. The air-droplet system is analyzed by solving the mass, momentum and energy conservation equations for each phase. The droplet phase is described by the Lagrangian approach. Two conditions of air flow in the smoke layer are assumed. Firstly, as commonly used in modeling fire suppression by water spray, the smoke layer is assumed to be quiescent. Secondly, both gas cooling effect and air entrainment in the water spray cone are inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…The results of the analysis using the proposed model are compared with their results and presented in Figure . The results of the proposed model, in first case, are almost identical with the results by Li and Chow . However, the analysis by Li and Chow predicted slower evaporate rate, in second case, compared to the prediction of that by the proposed model.…”
Section: Use Of the Model As A Validation Toolsupporting
confidence: 76%
See 2 more Smart Citations
“…The results of the analysis using the proposed model are compared with their results and presented in Figure . The results of the proposed model, in first case, are almost identical with the results by Li and Chow . However, the analysis by Li and Chow predicted slower evaporate rate, in second case, compared to the prediction of that by the proposed model.…”
Section: Use Of the Model As A Validation Toolsupporting
confidence: 76%
“…However, the analysis by Li and Chow predicted slower evaporate rate, in second case, compared to the prediction of that by the proposed model. It may be primarily due to the fact that Li and Chow did not consider the contribution of radiation emanating by a flame and the surrounding boundary walls on the evaporation of droplet. However, flame and the boundary walls emanate a substantial amount of energy through radiation.…”
Section: Use Of the Model As A Validation Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…due to turbulence and non-linear variation of physical properties [18]. However, we do not pursue complex simulations of individual detailed interactions among droplets.…”
Section: Model Assumptionsmentioning
confidence: 99%
“…In the literature, many studies are found on the topic of interaction of water droplets with fire smoke layer [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The cooling effect and drag force produced by water droplets are considered generally to yield smoke logging [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%